2015
DOI: 10.1016/j.epsl.2015.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous low frequency earthquakes and implications for deep San Andreas Fault slip

Abstract: Low Frequency Earthquakes (LFEs) are slip events that occur repeatedly at source locations within the lower crust. LFEs, and the associated seismic broadcast known as tremor, have been observed in a diverse array of tectonic environments. Here we develop a suite of statistical tools to conduct a systematic study of the spatial and temporal correlations of the event occurrence patterns of the 88 LFE sources beneath the greater Parkfield section of the San Andreas Fault. We first examine correlations in the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 32 publications
11
34
0
Order By: Relevance
“…Assuming a constant stress drop results in a scaling of 0.19, inconsistent with either of the previously proposed scalings. Increasing C by a factor of 5 for the episodic families (which corresponds to an effective stress of 5 MPa) results in maximum length scales on the order of tens of kilometers, which is consistent with the spatial extents inferred from other studies (Shelly, 2015;Trugman et al, 2015;Wu et al, 2015). We determine length scales of creep events by taking the values shown in Table 1, C = 0.047 GPa/m (assuming an effective stress of 1 MPa), and = 30 GPa.…”
Section: Moment-duration Scaling Of Creep Eventssupporting
confidence: 81%
See 3 more Smart Citations
“…Assuming a constant stress drop results in a scaling of 0.19, inconsistent with either of the previously proposed scalings. Increasing C by a factor of 5 for the episodic families (which corresponds to an effective stress of 5 MPa) results in maximum length scales on the order of tens of kilometers, which is consistent with the spatial extents inferred from other studies (Shelly, 2015;Trugman et al, 2015;Wu et al, 2015). We determine length scales of creep events by taking the values shown in Table 1, C = 0.047 GPa/m (assuming an effective stress of 1 MPa), and = 30 GPa.…”
Section: Moment-duration Scaling Of Creep Eventssupporting
confidence: 81%
“…Using equation (10), = 0.98, the median value for the episodic families, and taking the shear modulus in the source region to be 30 GPa results in a creep patch dimension of ≈30 km, consistent with the estimates of Shelly (2015) and Trugman et al (2015) deduced from the spatiotemporally coherent occurrence of the LFE families. Using equation (10), = 0.98, the median value for the episodic families, and taking the shear modulus in the source region to be 30 GPa results in a creep patch dimension of ≈30 km, consistent with the estimates of Shelly (2015) and Trugman et al (2015) deduced from the spatiotemporally coherent occurrence of the LFE families.…”
Section: Creep Events and Interepisode Slipsupporting
confidence: 76%
See 2 more Smart Citations
“…These include characterizations of the effects of the nearby 2003 M 6.5 San Simeon earthquake and the 2004 M 6.0 Parkfield earthquake [ Shelly and Johnson , ; Johnson et al , ], triggering by dynamic stresses of teleseismic and occasionally regional earthquakes [ Peng et al , ; Shelly et al , ; Peng et al , ; Hill et al , ; Peng et al , ], and modulation by tidal forces [ Thomas et al , ; van der Elst et al , ]. Additionally, multiple studies have examined the interactions and observed migration among LFE sources [ Wu et al , , ; Shelly , ; Trugman et al , ]. This LFE catalog has also been used to constrain physical models of tremor occurrence [ Daub et al , ] and to infer fault rheological properties [ Beeler et al , ].…”
Section: Introductionmentioning
confidence: 99%